Is serum bilirubin level a predictor factor in parotid gland carcinoma? - Bulğurcu,Suphi (2020)
Abstract Introduction: Bilirubin levels have been associated with risk of several malignancies. The association between pretreatment serum bilirubin levels and overall survival of patients with parotid gland carcinoma is unclear. Objectives: In this study, we assessed the effect of serum bilirubin levels to overall survival in malignant parotid tumors. Methods: This study included a total of 35 patients, 15 female and 20 male. The mean age of these patients was 60.7 ± 14.5 years. All patients who were diagnosed with parotid gland carcinoma and underwent total parotidectomy between 2008 and 2018, were retrospectively assessed. The relationship between the overall survival of patients and total bilirubin, direct bilirubin, and indirect bilirubin levels was estimated. The receiver operating characteristic (ROC) curve analysis was performed to determine the optimal cut-off points. Results: Patients with low direct bilirubin, total bilirubin and indirect bilirubin had significantly longer overall survival than those with high levels. Cut-off values for total bilirubin, direct bilirubin and indirect bilirubin were detected as 0.545 mg/dL, 0.175 mg/dL and 0.435 mg/dL, respectively. Conclusion: In our study, we observed that increased preoperative bilirubin levels are associated with reduced survival time in the postoperative period of patients with parotid gland carcinoma.